2021
DOI: 10.1155/2021/5569054
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase Inhibitory and Antioxidant Activity of the Compounds Isolated from Vanda roxburghii

Abstract: Vanda roxburghii has been used in traditional medicine to treat nervous system disorders including Alzheimer’s disease (AD). We reported earlier a high acetylcholinesterase inhibitory and antioxidant activity in the chloroform fraction of this plant. Therefore, this study was designed to explore the compounds with acetylcholinesterase inhibitory and antioxidant activities from the chloroform fraction of Vanda roxburghii. Phytochemical investigation led to the isolation for the first time of a fatty acid ester:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Literature is replete with information about in vivo and in vitro antioxidant and anti‐cholinesterase inhibition activities of components derived from plant sources. A few examples include powdered Psoralea corylifolia fruits (Gauresh et al, 2015), flower extracts from Nymphaea pubescens (Acharya et al, 2018), Anthocleista vogelii leaf extracts (Ajayi et al, 2019), essential oils from Lippia thymoides (Silva et al, 2019), and roots from Vanda roxburghii (Ahammed et al, 2021). Natural peptides from plant sources have been shown to display antioxidant and neurodegenerative modulating properties with a positive impact in terms of preventive and therapeutic measures (Prasasty et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Literature is replete with information about in vivo and in vitro antioxidant and anti‐cholinesterase inhibition activities of components derived from plant sources. A few examples include powdered Psoralea corylifolia fruits (Gauresh et al, 2015), flower extracts from Nymphaea pubescens (Acharya et al, 2018), Anthocleista vogelii leaf extracts (Ajayi et al, 2019), essential oils from Lippia thymoides (Silva et al, 2019), and roots from Vanda roxburghii (Ahammed et al, 2021). Natural peptides from plant sources have been shown to display antioxidant and neurodegenerative modulating properties with a positive impact in terms of preventive and therapeutic measures (Prasasty et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Vanillin and syringaldehyde are two common phenolic compounds found in nature. The compounds have shown earlier the antioxidant and anti-inflammatory activity in different in vitro model (Ahammed et al, 2021;Salau et al, 2020;Shahzad et al, 2018). Using the carrageenan-induced hind paw edema model we report here that these two compounds have similar anti-inflammatory activity.…”
Section: Anti-inflammatory Activity Of the Chloroform Fractionmentioning
confidence: 61%
“…The therapeutic uses of this plant have been documented in Unani and Ayurvedic systems of medicines. We reported earlier that the plant has high phenolic content and antioxidant activity, and possesses cholinesterase inhibitory potential Ahammed et al, 2021). In a preliminary study, we observed the antiinflammatory activity in the crude extract of the plant and the activity was high in the chloroform fraction among other fractions examined .…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations